STRATEGI PENGEMBANGAN KOMODITI TANAMAN PERKEBUNAN DI KABUPATEN KONAWE SELATAN - Heriono Heriono; M. Tufaila Hemon; Lukman Yunus (Jurnal Perencanaan Wilayah, 2018)
The potential of plantations can be developed as one of the assets of excellence in regional developmentprograms melalaui decentralization policy that can be used as part of the plantation sector for the economycontributes to effective contribution of plantations as a source of localrevenue Konsel. The purpose of this studywas to determine the commodity plantation crops and plantation crops commodity development strategies inKonsel. The data used in this research is secondary data obtained from multiple sources by taking the existingstatistical data and other documents relevant and necessary.This study was conducted in Konsel, from October to November 2015 regarding the developmentstrategy for the commodity of plantation crops in Konsel. The data used in this research is secondary dataobtained from multiple sources by taking the existing statistical data and other documents relevant andnecessary The results of this study indicate that: (1) The main commodity of plantation crops in Konsel that canbe developed in 2010-2014 was an average oil commodity LQ value of 1,136% cacao / cocoa amounted to1.214% and 1.5612% of the pepper plant. (2) Commodity crop plantations have direct relevance to future valueis the highest coconut,Suggestions for Konsel government needs to focus on the development of the leading sectors as sectors(agriculture, plantation, animal husbandry, forestry, and fisheries), (mining and quarrying) and (Trading,andindustrial). In order to develop Konsel particularly necessary strategies and policies appropriate to thedevelopment of both the leading commodity and not a feature.Keywords: Commodity Crops Development Strategy